Injuries and Violence in Sports: “What Happens on the Court Stays on the Court?” - Norvidaitė, Ieva; Biečiūtė, Patricija; Lapis, Vilius (Vilnius University Open Series, 2024)
The article analyzes the problem of violence used during sports and the legal and medical assessment of such actions in society. For this purpose, the legal doctrine in the context of health impairment during sports is examined, the criminal law and other legal acts regulating sports relations are evaluated. Also analyzed is the extremely scarce case law, which assesses the damage caused to athletes during sports and the responsibility for it. Finally, medical criteria are also evaluated - the specifics of the injuries that usually occur during sports and competitions, their features and possible consequences, which, in most cases, lead to the end of an athlete‘s career. One cannot disagree that sport is an extremely useful activity for individuals whose participants often lack legal clarity regarding the legal responsibility for their actions. Meanwhile, health impairment caused by violation of sports rules is undesired result, especially if done on purpose. Taking this into account, the article fraises fundamental questions – is damage in sports tolerable from the state‘s point of view, and which is not only intolerable, but for which it is perhaps necessary to apply the strictest type of legal responsibility – criminal responsibility?
Keywords: sport; violence; health impairment; sports competitions; medicine; damage; criminal liability; sports law